Implementasi Perlindungan Konstitusi dalam Hak Pendidikan bagi Kaum Disabilitas pada Sarana Pedidikan Perguruan Tinggi Negeri Islam - Ananda, Arif Firdaus; Muchlisin, Ahmad; Albab, Mas Ulul (Fakultas Syariah INSURI Ponorogo, 2023)
The Indonesian people have equal rights in education, including disabled people. The realization of constitutional guarantees for the education of people with disabilities is strengthened by an additional legal basis in Article 10 of Law No. 8 of 2016 concerning disabilities. In Indonesia, this is still rare and may exist, but only in a few campuses, so it appears that there is neglect of the provisions contained in the constitution. This study aims to analyze the implementation of constitutional protection in the right to education for people with disabilities in educational facilities at Islamic State Universities. This research is a qualitative research with the type of empirical juridical case study related to the application of the law and constitution of this country to education for persons with disabilities in higher education. This research was conducted on the UIN Sunan Ampel Surabaya campus, precisely at the Faculty of Sharia and Law. The results of this study found that the existing rules and conditions in the field have not been implemented due to many factors, which in general are still related to the bureaucracy in this country.